2018
DOI: 10.1002/hbm.24202
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal dynamics of resting‐state brain networks improve single‐subject prediction of schizophrenia diagnosis

Abstract: Correlation in functional MRI activity between spatially separated brain regions can fluctuate dynamically when an individual is at rest. These dynamics are typically characterized temporally by measuring fluctuations in functional connectivity between brain regions that remain fixed in space over time. Here, dynamics in functional connectivity were characterized in both time and space. Temporal dynamics were mapped with sliding-window correlation, while spatial dynamics were characterized by enabling network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 104 publications
(126 reference statements)
1
34
0
Order By: Relevance
“…In this study, we provided a novel characterization of these disturbances by explicitly modeling the dynamics of neural activity as a function of time, whereas most previous functional neuroimaging studies of schizophrenia have focused on static characterizations of activation and connectivity that represent time averages over the entire data acquisition interval. Furthermore, aberrant connectivity dynamics in the disorder are heritable (Su et al, 2016) and enable accurate, single-subject prediction of diagnostic status (Kottaram et al, 2018). Furthermore, aberrant connectivity dynamics in the disorder are heritable (Su et al, 2016) and enable accurate, single-subject prediction of diagnostic status (Kottaram et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we provided a novel characterization of these disturbances by explicitly modeling the dynamics of neural activity as a function of time, whereas most previous functional neuroimaging studies of schizophrenia have focused on static characterizations of activation and connectivity that represent time averages over the entire data acquisition interval. Furthermore, aberrant connectivity dynamics in the disorder are heritable (Su et al, 2016) and enable accurate, single-subject prediction of diagnostic status (Kottaram et al, 2018). Furthermore, aberrant connectivity dynamics in the disorder are heritable (Su et al, 2016) and enable accurate, single-subject prediction of diagnostic status (Kottaram et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Time-resolved analyses of functional connectivity in schizophrenia suggest that the disorder is characterized by reduced dynamism in connectivity (Miller et al, 2016), shorter dwell times in highly integrated states and altered thalamo-sensory dynamics . Furthermore, aberrant connectivity dynamics in the disorder are heritable (Su et al, 2016) and enable accurate, single-subject prediction of diagnostic status (Kottaram et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most dFC analysis techniques examine time-varying associations among the activation patterns of spatial networks while assuming that the spatial evolution of the networks is stationary. However, studies have shown that changes in functional connectivity patterns imply changes in the spatial networks [17], [18], [19]. Region of interest (ROI)-based analyses on resting-state networks (RSNs) have shown better classification of subjects when variability in both spatial and temporal domains is considered compared with variability assumed in either spatial or temporal domain [17], [18].…”
Section: Introductionmentioning
confidence: 99%